Assessment of Levels of Metabolic Hormones and Lipid Profile in Growth Hormone Deficient Patients - Al-hindawi, Ghada Kh.; Al-Lami, Makarim Q.; Al-Samarriae, Abdilkarim Y. (Iraqi Journal of Science, 2020)
AbstractThe current study aims to evaluate levels of metabolic hormones and lipid profile in a sample of growth hormone (GH) deficient patients. Seventy five GH deficient patients and twenty healthy subjects used as control group have been participated in this study during their attendance to the National Diabetic Center for Treatment and Research/Al-Mustansiriya University. The studied subjects’ ages were with a range (3-15 years). Blood samples were collected from the studied subjects to determine levels of basal GH, GH2 and GH3 after 1 hr and 1/30 hr provocation with clonidine, respectively; insulin like growth factor (IGF-1); levels of metabolic hormones [thyroid profile: triiodothyronine (T3), thyroxin (T4), and thyroid stimulating hormone (TSH)]; and lipid profile [cholesterol, triglyceride, high density lipoprotein (HDL), low density lipoprotein (LDL) and very low density lipoprotein (VLDL)].The findings of the anthropometric measurements of the studied groups revealed that a non-significant (P>0.05) difference was found in the weight between the patients and the control, while the mean of height in the patients was significantly (P<0.05) lower than its value in the control. Mean of BMI detected a non-significant (P>0.05) difference between the patients and the control. While mean of BMI percentile and mean of BMI Z-score revealed significant (P<0.05) decrease in the patients compared to their values in the control.The results showed that non-significant (P>0.05) difference was found in level of basal GH between the patients and the control, while a high significant (P<0.01) decrease was found in levels of GH2 and GH3 in the patients group compared to the control group. Level of IGF-1 showed a significant (P<0.05) decrease in the patients compared to the control.The results of metabolic hormones revealed a non-significant (P>0.05) difference in serum T3 between the patients and the control, while a high significant (P<0.01) decrease was found in serum T4 in the patients compared to the control. A non-significant (P>0.05) difference was found in serum TSH between the patients and the control. The data of serum cortisol showed a significant (P<0.05) increase in the patients compared to the control.The results of lipid profile showed a non-significant (P>0.05) difference in serum cholesterol between the patients and the control, while triglyceride showed a significant (P<0.05) increase in the patients compared to the control. A non-significant (P>0.05) difference was found in serum HDL between the patients and the control, while a significant (P<0.05) increase was found in levels of LDL and VLDL in the patients compared to the control.It can be concluded from the present study that diagnosis of GHD cannot be done at the basal serum of GH. A high level of GH was detected after 1 hr. provocation with clonidine compared with its value after 1/30 hr. provocation. The IGF-1 is an appropriate parameter to expect GHD in children and adolescences whom GHD was detected by GH stimulation testing. Low GH secretion is associated with high level of cortisol resulting in GHD. Patients with GHD displayed a tendency towards lipids disturbances.